PERAN ORANG TUA DALAM PROSES BIMBINGAN DAN KONSELING ANAK - Aryanto, Randy; Yulianti, Yulianti; Hasanah, Uswatun Dwi; Simanullang, Adelina Rodia (Dharmas Education Journal (DE_Journal), 2023)
Providing parental guidance and counseling services to the younger generation or their children is so that they can develop their abilities, adapt to the social environment, educational environment and future profession, prepare strategic plans for study, career development and future life. future. . parents are very important. It is important for children because it is parents who look after and guide their children by providing good examples in everyday life, and parents introduce their children to things that exist in this world and answer questions about things that children do not do. his son. understand. . The role of parents in understanding a child's character is: a) Both parents should love their child and look after their child, when the child gets enough love from his mother and father, so that when he is outside and facing new problems. , they can deal with it. and fix it. b) parents must remain calm at home so that children will feel calm at home, c) mutual respect between parents and children, d) parents must be able to act more firmly so that they will respect children, build trust, gratitude and give confidence in children, e) reduce bad words because it affects their personality and creates closeness, familiarity, 6) strengthen self-confidence because in this way they will easily accept their mistakes and errors, they believe that it is their own capacity to help others, they felt his presence was very meaningful. important. useful and important, f) gathering with children, in order to see children's curiosity about the truth which they have brought from birth, at their still early age, usually curious about themselves, that's why the role of parents towards children is very important.